2007
DOI: 10.1111/j.1365-2613.2007.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

BALB/c mice resistant to Toxoplasma gondii infection proved to be highly susceptible when previously infected with Myocoptes musculinus fur mites

Abstract: The immune response induced by Toxoplasma gondii is characterized by Th1 immune mechanisms. We previously demonstrated that C57BL/6 mice infested with Myocoptes musculinus and infected with T. gondii by intraperitoneal route undergo accelerated mortality according to Th2 immune mechanisms induced by the acarian. To evaluate whether infection with M. musculinus influences T. gondii-induced Th1 response in a resistant mouse lineage, BALB/c, which develops latent chronic toxoplasmosis in a way similar to that obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…The up-regulation of IL-4 in a Toxoplasmainfected host indicates the host is susceptible to the parasite, even if it is previously deemed to be resistant to the organism (Welter et al 2007). …”
Section: Toxoplasma-infected Macrophages Induce the Production Of Ifnmentioning
confidence: 99%
“…The up-regulation of IL-4 in a Toxoplasmainfected host indicates the host is susceptible to the parasite, even if it is previously deemed to be resistant to the organism (Welter et al 2007). …”
Section: Toxoplasma-infected Macrophages Induce the Production Of Ifnmentioning
confidence: 99%
“…T. gondii infection modulates both immune responses and outcomes of many concomitant infections and tumors. The outcome of T. gondii infection has been reported to be modulated substantially by presence of either prior infections or concomitant infections [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Earlier studies have attributed a variety of different findings to T. gondii infection (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Infested mice may also be prone to secondary infections, reduced life span, and decrease of body weight (WELTER et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Fur mites infestations in research colonies remain a constant management challenge. Fur mites have been reported to interfere with established research models by directly potentiating allergictype hypersensitivity reactions (MORITA et al, 1999), indirectly interfering with normal immune responses to other (WELTER et al, 2007) and have been shown to provoke a Th2 immune response and elevate serum IgE (LALTOO et al, 1979;JUNGMANN et al, 1996).…”
Section: Introductionmentioning
confidence: 99%